ANALISIS KUALITAS PELAYANAN TERHADAP KEPUASAN JEMAAH UMRAH DI PT. SMEVA HOLIDAY PEKANBARU - Suganda, Apriani; Yurizal, Firdaus (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2025)
This study aims to explain and determine the extent of the influence of service quality on the satisfaction of umrah pilgrims at PT. Smeva Holiday Pekanbaru both simultaneously and partially and also see which variables have a dominant influence on the satisfaction of Umrah pilgrims. The independent variables used in this study are Tangible, Reliability, Responsiveness, Assurance and Empathy. While the dependent variable is the satisfaction of the pilgrims. The location of this study is PT. Smeva Holiday Pekanbaru. The sampling technique uses Probability Sampling with a sample size of 150 respondents. From the results of the F test that has been carried out, it shows that the service quality variables consisting of Tangible, Reliability, Responsiveness, Assurance and Empathy have a joint influence on the satisfaction of Umrah pilgrims with a sig. F value of 0.000